2020
DOI: 10.1088/1361-665x/ab87e4
|View full text |Cite
|
Sign up to set email alerts
|

Tunable arc-shaped acoustic metasurface carpet cloak

Abstract: In this paper, a tunable arc-shaped acoustic metasurface (AAM) carpet cloak has been proposed and systematically investigated. The AAM carpet cloak consists of covers, rotors, bolts and nuts. The rotors can be rotated continuously within the covers to form a reconfigurable hook channel mechanism. By setting various rotational angles, we construct two-dimensional (2D) tunable AAM carpet cloaks to achieve excellent stealth performances under different operating conditions. Numerical simulations and experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Thanks to their thinness which is usually in the sub-wavelength, AMs have added value and functionalities in comparison with other acoustic metamaterials with small footprint (Xie et al, 2014;Cheng et al, 2015;Zhao et al, 2017;Assouar et al, 2018;Quan and Alu, 2019). Numerous exotic acoustic phenomena such as sound cloaking (Faure et al, 2016;Ma et al, 2019;Fan et al, 2020;Zhou et al, 2020), sound splitting (Zhai et al, 2018;Ding et al, 2021), sound absorption (Ma et al, 2014;Song et al, 2019;Liu et al, 2021;Li et al, 2022a;Guo et al, 2022), anomalous reflection or refraction (Diaz-Rubio and Tretyakov, 2017;Li et al, 2019a;Zhu and Lau, 2019;Li et al, 2020a;Chiang et al, 2020;Song et al, 2021), sound focusing (Zhu et al, 2016a;Lombard et al, 2022), one-way sound propagation (Zhu et al, 2015;Jiang et al, 2016), and medical ultrasound (Tian et al, 2017;Hu et al, 2022) have been proposed and demonstrated using AMs. AMs possess unusual features, including selective focusing and negative refraction, are enabled by the generalized Snell's law, which adds a new degree of freedom to control the behavior of transmitted or reflected waves by incorporating a lateral momentum (Yu et al, 2011) (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to their thinness which is usually in the sub-wavelength, AMs have added value and functionalities in comparison with other acoustic metamaterials with small footprint (Xie et al, 2014;Cheng et al, 2015;Zhao et al, 2017;Assouar et al, 2018;Quan and Alu, 2019). Numerous exotic acoustic phenomena such as sound cloaking (Faure et al, 2016;Ma et al, 2019;Fan et al, 2020;Zhou et al, 2020), sound splitting (Zhai et al, 2018;Ding et al, 2021), sound absorption (Ma et al, 2014;Song et al, 2019;Liu et al, 2021;Li et al, 2022a;Guo et al, 2022), anomalous reflection or refraction (Diaz-Rubio and Tretyakov, 2017;Li et al, 2019a;Zhu and Lau, 2019;Li et al, 2020a;Chiang et al, 2020;Song et al, 2021), sound focusing (Zhu et al, 2016a;Lombard et al, 2022), one-way sound propagation (Zhu et al, 2015;Jiang et al, 2016), and medical ultrasound (Tian et al, 2017;Hu et al, 2022) have been proposed and demonstrated using AMs. AMs possess unusual features, including selective focusing and negative refraction, are enabled by the generalized Snell's law, which adds a new degree of freedom to control the behavior of transmitted or reflected waves by incorporating a lateral momentum (Yu et al, 2011) (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these restrictions, the emergence of acoustic metamaterials [14][15][16][17][18][19][20] and metasurfaces [21][22][23][24][25][26][27] have provided alternative design schemes for passive acoustic lenses of vortex beams. As examples, by designing thickness-gradient structures [28,29] or an acoustic plate with a spiral shaped structure [30][31][32], the acoustic vortex beam can be observed around structure surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…
particular have been the focus of recent research, [20,21] with demonstrations of acoustic cloaking, [22][23][24][25] selective absorption, [26][27][28] focusing, [29][30][31][32][33][34] reflected wavefront manipulation, [35][36][37][38] passive phased array, [39] and acoustic holography. [40][41][42] These applications are generally realized by arraying metasurface units across an interface, resulting in spatially defined phase and/or amplitude modulation.
…”
mentioning
confidence: 99%